Observer-based friction force estimation for brake system under low-frequency vibration. (July 2022) - Qian, Lu; Zhao, Xingwei
Creep groan is a low-frequency vibration, which is produced by the stick–slip motion from the pad–disc contact in the brake. Friction plays a key role in generating the stick–slip motion. However, directly measuring the friction force in an actual brake system is difficult. Therefore, force estimation methods are proposed to estimate the friction force based on unknown input observers. A proportional integral observer is applied to estimate the friction force amplitude from the torsional angle of the driven shaft. An approximate H2 observer is designed to distinguish the stick region and slip region from the acceleration of the pad. Different from modeling methods, designing observers do not introduce modeling deviation and have a relatively low requirement on parameter identification. In addition, the observer methods can extract more detailed information of friction force than modeling methods. The observed friction force can be considered an index to evaluate the severity of the brake defect. The performance and effectiveness of the proposed methods are confirmed by experiments on a brake test rig.